KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN BAHASA INDONESIA - Basuki, Basuki; Suryani, Yulinda Erma; Setiadi, Dwi Bambang P (LITERA, 2017)
Abstract This study aims to describe students’ learning difficulties in the Indonesian language learning process at the senior high school. The research subjects were students of SMAN 1 Klaten, SMAN 1 Karangnongko, and SMAN 1 Karangdowo. The data were collected by means of tests and interviews. They were analyzed using qualitative and quantitative descriptive techniques with the AnBuso computer program. The results of the data analysis show that the students have difficulties in: the language sub-competencies of structure (61.07%) and vocabulary (52.6%); the language competencies of listening (41.88%), speaking (18.89%), reading (21.15%), and writing (20.02%); and the literary competency at the levels of information (45.69%), concepts (40.9%), perspectives (41.74%), and appreciation (47.1%). These show that the difficulties are evenly distributed on the various components of learning materials, both for language and literary competencies, so that the solutions must be comprehensive including the selection of learning methods. Keywords: learning difficulties, competencies, Indonesian language